2006
DOI: 10.1111/j.1540-5414.2006.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplier‐Switching Inertia and Competitive Asymmetry: A Demand‐Side Perspective*

Abstract: Building on strategic management, operations strategy, and supplier management literatures, this article presents a framework for supplier selection from the demand-side perspective. We highlight the role of a purchasing firm's switching inertia in the supplierselection process and demonstrate the usefulness of our framework for the industrial automation industry. Empirical data for this study was collected from 171 corporate and plant-level executives in pharmaceutical, chemical, and paper-and-pulp manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 94 publications
0
45
0
Order By: Relevance
“…This research method also shed light on issues related to the timing of the next generation of high technology products (Kim and Srinivasan, 2006). Additionally, conjoint analysis has been used to assess tradeoffs and switching inertia associated with supplier selection (Verma and Pullman, 1998;Li et al, 2006). Other applications have focused on optimal service design considering operational difficulty (Verma et al, 2001) and operations capacity (Pullman and Moore, 1999;Goodale et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This research method also shed light on issues related to the timing of the next generation of high technology products (Kim and Srinivasan, 2006). Additionally, conjoint analysis has been used to assess tradeoffs and switching inertia associated with supplier selection (Verma and Pullman, 1998;Li et al, 2006). Other applications have focused on optimal service design considering operational difficulty (Verma et al, 2001) and operations capacity (Pullman and Moore, 1999;Goodale et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a strong affinity for existing relationships predicated on internal combustion vehicles and a tendency to resist the discontinuation of the existing relationships with automakers (Kim et al, 2006;Li et al, 2006). These tendencies counter the development of predictions favouring the uptake of emerging technologies.…”
Section: Vertical Communication Between Automakers and Suppliersmentioning
confidence: 87%
“…Reliability on the part of the vendor in providing a more consistent supply is an important factor in a food retailer's assessment of which suppliers to use. As research findings consistently show, product quality (performance criterion), price (economic criterion), delivery reliability (adaptive criterion), and customer preference (integrative criterion) are the most important attributes considered in the comparative evaluation and choice of a supplier (Braglia and Petroni 2000;Li et al 2006;Narasimhan, Talluri, and Mahapatra 2006).…”
Section: Consumer Attitudesmentioning
confidence: 88%
“…For example, Braglia and Petroni (2000) suggested that in selecting suppliers, evaluations of predetermined choice criteria and comparisons among qualifying suppliers should be examined. Thus, the supplier selection process involves multi-attribute levels (Li et al 2006). Fundamental concepts like establishing mutual trust (Dawson and Shaw 1989); enhancing service quality (de Ruyter, Wetzels, and Lemmink 1996); pricing (Johan and Gripsrud 1981); and reducing risk (McGoldrik and Douglas 1983) are important in retailers' vendor selection decisions.…”
Section: Supplier Choice Criteria Theorymentioning
confidence: 99%